Laporan Praktikum Pengabdian Masyarakat Gerakan Bersih Lingkungan Bersama Anak Muda dalam Aksi Nyata Desa Pagar Gunung - Wahidah Rangkuti; Khodma Siah; Syaipullah Ahmad; Elismayanti Rambe (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2025)
This report is entitled "Clean Environment Movement with Young People in Real Action in Pagar Gunung Village," which aims to increase public awareness of the importance of maintaining environmental cleanliness. Through initial observations, problems related to indiscriminate waste disposal were found. The methods used include problem identification, socialization, and implementation of the provision of temporary waste disposal sites (TPS) and mutual cooperation activities. The results of the activities show an increase in public awareness and active participation of young people in maintaining environmental cleanliness, which has an impact on cleaner and healthier environmental conditions. The conclusion of this activity is the importance of community collaboration in environmental conservation efforts, as well as the need for ongoing support to maintain village cleanliness.